Warm-up durations in a hot-dry climate affect thermoregulation, mean power-output and fatigue, but not peak power in specific soccer repeated-sprint ability - Frikha, M.; Chaâri, N.; Said, N. B.; Alibrahi, M. S. (BMC Sports Science, Medicine and Rehabilitation, 2020)
Background: This study addressed the lack of data on the effect of warm-up (WU) duration in hot-dry climate (~ 30 °C; ~ 18% RH), on thermoregulation, muscular power-output, and fatigue after specific soccer repeated-sprint test (RSA). Methods: Eleven amateur soccer players participated in a cross-over randomized study and they underwent the Bangsbo repeated-sprint test, after three WU durations (i.e. WU10, WU15 and WU20 min) at 70% of MAV, and on different days. Peak power (PP), mean power (MP) and the fatigue index (FI) were recorded and analyzed. Likewise, heart rate (HR), tympanic temperature (Ttym), mean body temperature (MBT) and rating of perceived exertion (RPE) were recorded during each session. Results: The repeated measure ANOVA showed that MP improved after WU15 in comparison to WU10 and WU20 (p = 0.04 and p = 0.001; respectively). Nonetheless, no significant effect on PP was recorded after all WU durations. FI during RSA increased after WU20 in comparison to WU15 and WU10 (p < 0.001 and p = 0.003; respectively). Higher RPE values (p < 0.001) were recorded after WU15 and WU20 in comparison to WU10 duration. The two-way ANOVA showed higher ?Ttym and ?MBT values after WU15 and WU20 compared to WU10 (p = 0.039 and p < 0.001for Ttym; p = 0.005 and p < 0.001 for MBT, respectively). Conclusions: The WU15 at 70% of MAV better assists mean power-output during soccer RSA in hot-dry (~ 30 °C; 18% RH) climate, but not peak power. Reducing WU duration up to 10 min seems to be insufficient to induce beneficial physiological changes necessary for optimizing repeated-sprint performance, while its extension up to 20 min remains detrimental for muscular power and induces higher fatigue.